ON THE TAXONOMIC POSITION AND DISTRIBUTION OF THE GENUS BORISSIAKOCERAS ARKHANGELSKY, 1916 (AMMONOIDEA) - Mikhailova I.A.; Naidin D.P. (My University, 2002)
The morphogenesis of the genus Borissiakoceras is studied on the basis of material from the Taimyr Peninsula. The stratigraphie and geographic distribution of the genus are discussed, and a systematic description is provided.